2011
DOI: 10.1121/1.3646902
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the perceived sound of trauma-induced tinnitus in gerbils

Abstract: Tinnitus often develops following inner ear pathologies, like acoustic trauma. Therefore, an acoustic trauma model of tinnitus in gerbils was established using a modulated acoustic startle response. Cochlear trauma evoked by exposure to narrow-band noise at 10 kHz was assessed by auditory brainstem responses (ABR) and distortion product otoacoustic emissions (DPOAE). Threshold shift amounted to about 25 dB at frequencies > 10 kHz. Induction of a phantom-noise perception was documented by an acoustic startle re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 46 publications
4
26
1
2
Order By: Relevance
“…Several recent studies have reported behavioral evidence of tinnitus in mice (26, 66, 75), rats (40), gerbils (76), and guinea pigs (34, 57) following noise exposure leading to temporary shifts in hearing thresholds. Tinnitus-like behavior was reported for the majority, but not all of the animals (26, 34, 40).…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have reported behavioral evidence of tinnitus in mice (26, 66, 75), rats (40), gerbils (76), and guinea pigs (34, 57) following noise exposure leading to temporary shifts in hearing thresholds. Tinnitus-like behavior was reported for the majority, but not all of the animals (26, 34, 40).…”
Section: Discussionmentioning
confidence: 99%
“…Since then a number of different laboratory animal species and various strains have been used for the behavioral assessment of tinnitus. Besides the laboratory rat ( Rattus norvegicus ) [851], these include the domestic house mouse ( Mus musculus ) [5258], the chinchilla ( Chinchilla laniger ) [59, 60], the Syrian golden hamster ( Mesocricetus auratus ) [6164], the guinea pig ( Cavia porcellus ) [6567], and the Mongolian gerbil ( Meriones unguiculatus ) [68, 69]. Since the early studies by Jastreboff et al, the laboratory rat remains the most prominent species used for investigating tinnitus at the behavioral level.…”
Section: Species Used For Behavioral Testing Of Tinnitusmentioning
confidence: 99%
“…The second established method for inducing tinnitus in behavioral models is through acoustic trauma [8, 15, 20, 21, 23, 2527, 30, 31, 37, 3942, 4649, 5156, 5966, 68, 69, 107]. It is assumed that a cochlear damage is in most cases the trigger for a sequence of events leading to the development of tinnitus in humans.…”
Section: Established Ways Of Tinnitus Induction In Animal Researchmentioning
confidence: 99%
See 2 more Smart Citations